Perlindungan Otoritas Jasa Keuangan Terhadap Kerahasiaan dan Keamanan Data Pribadi Nasabah Bank - Rani, Marnia (Jurnal Selat, 2014)
Banking activities conducted based on the Principle of Fiduciary between the bank and its customers. Society will entrust his money to the bank if the bank can provide a guarantee that all the information about the customer can be kept confidential by the bank. To maintain customer confidence in the bank in carrying out business activities must also apply the principle of confidentiality. The principle applied by the bank secrecy is a form of commitment and bank protection in keeping customers personal data. However, what happens today is that many people who complain of financial institutions that offer their products through long-distance phone lines (telemarketing). This is a big question that customers experiencing financial services product offerings through the phone line. Customers generally concluded unilaterally that the banks where they deposit funds, have provided their personal data to other parties (financial institutions). This is of course contrary to the principles of fiduciary and confidentiality that must be firmly held by the bank as a financial institution that is dependent on the source of funds from the public (depositors). Protection of confidentiality of customers personal data, in addition to the duty of the bank, also the responsibility of policy makers in the banking business. Birth of Law Number 21 Year 2011 concerning the Financial Services Authority, authorizes the protection of the confidentiality of customers personal data, which had previously been the Bank Indonesias duty, then switching function to the Financial Services Authority. Financial Services Authority as an agency that has the task of regulating and supervising the financial services institution, is able to provide legal protection for the consumer in this case bank customers, so as to foster consumer confidence in the financial institution.  Keywords: Financial Services Authority, Confidentiality Principles/Bank Secrecy Principle, Customer Personal Data